Genetic divergence in fenugreek (Trigonella foenum-graecum L.) germplasm - O P Balai, K N Shiva, U K Jain, Dhirendra Singh, (Journal of Spices and Aromatic Crops, 2006)
Thirty six genotypes of fenugreek (Trigonella foenum-graecum ) were studied at Jobner(Rajasthan) for their genetic divergence following D2 analysis. The study indicated that thegenotypes were grouped into six clusters and there was lack of parallelism between geneticand geographic diversity. Intra cluster distance was highest in cluster I followed by clusterII. Inter cluster distance was maximum between cluster IV and II followed by III and II.Among the 10 characters studied for genetic divergence, fat content contributed the maxi-mum accounting for 70.3% of total divergence, followed by plant height (8.6%). The studyindicated that for obtaining heterotic response as well as better segregants, inter-matingbetween genotypes of diverse clusters may be undertaken in breeding programmes for im-proving yield and quality traits.